Gastric Organoids: Progress and Remaining ChallengesSummary - Min-Jiao Pang (Elsevier, 2022)
The stomach is a complex and physiologically necessary organ, yet large differences in physiology between mouse and human stomachs have impeded translation of physiological discoveries and drug screens performed using murine gastric tissues. Gastric cancer (GC) is a global health threat, with a high mortality rate and limited treatment options. The heterogeneous nature of GC makes it poorly suited for current “one size fits all” standard treatments. In this review, we discuss the rapidly evolving field of gastric organoids, with a focus on studies expanding cultures from primary human tissues and describing the benefits of mouse organoid models. We introduce the differing methods for culturing healthy gastric tissue from adult tissues or pluripotent stem cells, discuss the promise these systems have for preclinical drug screens, and highlight applications of organoids for precision medicine. Finally, we discuss the limitations of these models and look to the future to present potential ways gastric organoids will advance treatment options for patients with GC.